Climate Change and Environmental Conflict in The Lake Chad Region - Omosefe Oyekanmi (Universitas Medan Area, 2022)
Environmental conflicts manifest in different ways, with context-specific impacts on the affected regions. Emerging as a crucial point of national and international security, issues of climate change have taken the fore. In the Lake Chad Region, more people have become more susceptible to the climate change, given the poverty level, unemployment and inadequate governance in these regions. Christened as the world’s most complicated humanitarian disaster, the receding lake which has served as a major source of livelihood in time past is now a haven for violent conflict and extremist groups. Assuming top on the agenda of African Union (AU) Peace and Security Council and the UN Peacebuilding Commission meetings held in 2022, its importance cannot be underestimated. To this end, this paper strengthens the evidence on climate-related conflict in the Lake Chad Basin and its simultaneous effect on human security. Using qualitative method, data was gathered through secondary sources, such as journal articles, reports from the Lake Chad Basin Commission (LCBC), books and online sources on the subject matter. Data gathered were analyzed using content analysis. Findings reveals that the vulnerability of the area based on poverty, historical antecedents to conflict and crime, as well as the growing population makes the response to the receding lake naturally violent. It is recommended therefore, that the Lake should be revived and nourished by joint collaboration from states within the region and international actors as a long term plan. Also, resilient measures through employment opportunities and skilled training should be available for the youths and most vulnerable people.